Proceeding of LPPM UPN "VETERAN" Yogyakarta Conference Series 2020- Political and Social Science Series 2020
DOI: 10.31098/pss.v1i1.193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Marketing Capability Against Marketing Performance with Innovation as mediation (Study on Batik SMEs during the Covid-19 Pandemic)

Abstract: There The Covid-19 pandemic has an impact on SMEs in Bantul, Yogyakarta. During a pandemic, SMEs rely on digital marketing to access consumers. This study aims to examine the effect of digital marketing capabilities on innovation capabilities, the influence of digital marketing capabilities on marketing performance, and innovation capabilities on marketing performance. The research was conducted on SMEs that produce batik at the Giriloyo batik center and the Wijirejo batik center, Bantul, Yogyakarta. Responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Digital marketing is a big part of making sales happen. Utomo and Susanta also found that SMEs that made batik in Yogyakarta did better at marketing when they were good at marketing [1]. From this description, we can come up with the following hypothesis:…”
Section: Digital Marketing Capability and Marketing Performancementioning
confidence: 75%
See 1 more Smart Citation
“…Digital marketing is a big part of making sales happen. Utomo and Susanta also found that SMEs that made batik in Yogyakarta did better at marketing when they were good at marketing [1]. From this description, we can come up with the following hypothesis:…”
Section: Digital Marketing Capability and Marketing Performancementioning
confidence: 75%
“…Therefore, this research is also directed to determine the effect of innovation ability on marketing performance. Utomo & Susanta [1] have found that digital marketing capability and innovation capability have a significant effect on batik SMEs. Research in the culinary field is also important to get enough attention considering that there are far more of them.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, as in many parts of the world, the FMCG sector witnessed a surge in digital and online marketing innovations, as brands sought to maintain their market presence and cater to the evolving needs of consumers. Utomo and Susanta (2020) explored the impact of digital marketing capabilities on marketing performance, particularly focusing on Batik SMEs during the pandemic. Their findings underscored the significant role of digital marketing in driving business outcomes.…”
Section: Digital and Online Marketing Innovationsmentioning
confidence: 99%
“…Digital marketing capabilities significantly encourage SME performance in the digital era (MPmar et al, 2022). The ability to apply digital marketing creates product uniqueness in the form of innovation so that it becomes a company advantage that impacts company performance (Utomo & Susanta, 2020). Digital technology has revolutionized marketing rules and caused many conventional marketing techniques to become obsolete (Nuseir & Refae, 2022).…”
Section: The Relationship Between Digital Marketing Capability and Ms...mentioning
confidence: 99%